Teacher violence from the perspectives of teachers and students and related factors: A survey in Southern Iran - Ardestani, Zahra Foghara; Saber, Maryam; Dehghan, Mahlagha; Iranpour, Abedin; Baniasadi, Hamideh (Frontiers in Psychology, 2022)
Introduction Teacher violence is defined as the intentional use of power by teachers against students in a variety of ways, including physical, verbal, psychological, and sexual assault. Victims of school violence are more anxious and insecure than other students. An in-depth and comprehensive study on the prevention of violence in schools is urgent and necessary. We conducted this study to determine teacher violence from the perspectives of schoolteachers and students and related factors. Methods We conducted this descriptive-analytical study on 313 teachers and 400 students in Ardestan, southern Iran, in 2019. We selected teachers and students using a census method and stratified random sampling, respectively. The research instrument was the school violence questionnaire. Results From the perspective of teachers, the mean score of teacher violence (5.7) was significantly lower than that of students (18.3). Male, young, single teachers with diploma and less work experience had significantly higher violence scores than other teachers (P < 0.001). We witnessed this trend in public boys’ schools as well (p < 0.001). The total mean score for teacher violence was not significantly different between male and female students. From the perspective of students, the mean score of teacher violence was significantly different (P < 0.001). Conclusion Our results suggest that education authorities and school principals should supervise public school teachers with less education, younger students, and boys’ schools and provide practical training to improve the communication and emotional skills among these teachers.